A 5-year review of malaria surveillance in Kuching, Sarawak - Haironi, Y.; Kamaliah, MD (The International Medical Journal of Malaysia, 2014)
Background Malaria is endemic in Sarawak contributing to the highest incidence rate in Malaysia. Kuching division consists of three main areas, namely Kuching district, Lundu and Bau. This review aims to highlight the trends of malaria over the past five years in terms of demographic characteristics and vector control programmes and to identify factors that contribute to the difficulty in malaria control programme in this state.